Knighting Bert: Mackenzie King and Ottawa's Galahad Statue - Duffy, Dennis (Ontario History)

(untitled) (The Ontario Historical Society, 2012)
Mackenzie King's successful efforts to erect a statue in memory of Bert Harper's heroic, self-sacrificing rescue of a drowning girl is rich in cultural and political implications. The Sir Galahad statue abutting Parliament Hill was King's first melding of personal concerns with public commemoration. That foray into controlling public memory through public sculpture and construction was followed by grander ones: Kingsmere; the Pioneer Arch (Niagara Falls, demolished); and the William Lyon Mackenzie memorial (Queens Park, Toronto). King's Diary and relevant documents in Library and Archives Canada lay bare the ways in which the junior member of Cabinet and self-appointed chief mourner—in addition to authoring a printed hagiography (The Secret of Heroism)—engineered a bronze testimonial to his grief, and a memorial to an heroic civil servant.